The paradoxes of normalization: cannabis as nuisance crime, medicine, and consumer good in British Columbia before and after legalization - Wheeldon, Johannes (Deviant behavior, 2023)
In the space of two years, selling cannabis in Canada went from being a criminalized activity to an essential service. However, the broad recognition of its relative safety compared with other intoxicants and potential medical benefits are outpacing regulatory strategies to manage its responsible use. The paradoxical normalization of cannabis is based on its contested legal, moral, and cultural status. This paper makes three contributions. First, based on secondary data analysis, we present qualitative data from cannabis insiders in the province of British Columbia (B.C.), focused on their perceptions of cannabis as medicine, consumer good, and nuisance crime. Second, we consider tolerance and aversion related to cannabis normalization by linking the perceptions of these insiders with past and recent research. Finally, we argue that the lack of legal spaces to consume cannabis exacerbates concerns about impaired driving, nuisance crime, and stigmatization. Applying levels of stigma to areas of cannabis liberalization can assist efforts to describe the paradoxes of normalization. These appear to result from older protection-based policies, which may have the effect of prolonging what they seek to disrupt.